Prehospital characteristics, incidence trends, and outcome of emergency self‐inflicted injury patients with gas substances: a population‐based descriptive study in Osaka, Japan - Katayama, Yusuke (Acute Med Surg, 2019)
AIM: Little is known about the detailed characteristics of patients using gas substances for self‐inflicted injury in prehospital settings. The aim of this study was to investigate the characteristics, incidence trends, and outcomes of patients who used gas substances for self‐inflicted injury in Osaka City, Japan, using ambulance records. METHODS: This was a retrospective observational study that used data from 2009 to 2015. We extracted details from ambulance records of self‐inflicted injury patients who used gas substances. The annual incidence of self‐inflicted injury by gas substance and age group and Poisson regression models were applied for calculating the annual incidence trend by type of gas substance. The main outcome was confirmed death at the scene, and we also calculated the crude odds ratios and 95% confidence intervals for each gas substance. RESULTS: During the study period, there were 324 self‐inflicted injury patients who used gas substances. The most commonly used gases were carbon monoxide (CO) (54.9%), followed by hydrogen sulfide (12.7%), helium (6.5%). The incidence of CO and hydrogen sulfide have subsequently decreased (P for trend = 0.023 and <0.001, respectively); however, the incidence of helium did not change during the study period (P for trend = 0.586). The mortality rate was highest in patients who used helium (66.7% [14/21]) and the crude odds ratio of helium was 3.857 (95% confidence interval, 1.267–11.745; P = 0.017) compared with hydrogen sulfide. CONCLUSION: This study revealed that the incidence of self‐inflicted injury with helium did not change and its proportion of death at the scene was high in Osaka City.